An ecology of invention: for relational, situated, and diverse practices in sound creation and research - Padovani, José Henrique (ANPPOM, 2026)
The text departs from the field of the ecologies of music and sound to critique dualistic and decontextualized approaches to sound creation and investigation practices. The central objective is to advocate for paradigms for artistic practice and research that are based on the principles of relationality, situatedness, and diversity. The theoretical-methodological framework articulates concepts from sound ecology with those of the ecology of mind, individuation, and technodiversity, promoting a non-dichotomous reflection on the relationships between technology, nature, and culture. As a result, an ``ecology of invention’’ is proposed, in which technical, creative, and theoretical processes are configured from relational, situated, and diverse aspects, rejecting hegemonic and monolithic notions of nature, culture, and technology.